Deficiency of the Immunoproteasome LMP10 Subunit Attenuates Angiotensin II-Induced Cardiac Hypertrophic Remodeling via Autophagic Degradation of gp130 and IGF1R - Yan, Wen; Dong, Zhi-Chao; Wang, Jing-Jing; Zhang, Yun-Long; Wang, Hong-Xia; Zhang, Bo; Li, Hui-Hua (Frontiers in Physiology, 2020)
Abstract Background/Aim: Hypertensive cardiac hypertrophy is the leading cause of cardiac remodeling and heart failure. We recently demonstrated that the immunoproteasome, an inducible form of the constitutive proteasome, plays a critical role in regulating cardiovascular diseases. However, the role of the immunoproteasome LMP10 (β2i) catalytic subunit in the regulation of angiotensin II (Ang II)-induced cardiac hypertrophic remodeling remains unclear. Methods: Wild-type (WT) and LMP10 knockout (KO) mice were infused with Ang II 1000 ng/kg/min for 2 weeks. Blood pressure was measured using a tail-cuff system. Cardiac function and hypertrophic remodeling were examined by echocardiography and histological staining. The expression levels of genes and proteins were examined with quantitative real-time PCR and immunoblotting analysis, respectively. Results: LMP10 mRNA and protein expression was signiﬁcantly increased in Ang II-stimulated hearts and primary cardiomyocytes. Moreover, Ang II infusion for 2 weeks increased systolic blood pressure, abnormal cardiac function, hypertrophy, ﬁbrosis, and inﬂammation in WT mice, which were significantly reversed in KO mice. Moreover, a marked reduction in the protein levels of insulin growth factor-1 receptor (IGF1R), glycoprotein 130 (gp130) and phosphorylated AKT, mTOR, STAT3 and ERK1/2 and an increase in the LC3II/I ratio were also observed in LMP10 KO mice compared with WT mice after Ang II infusion. In vitro culture experiments confirmed that LMP10 knockdown activated autophagy and increased IGF1R and gp130 degradation, leading to the inhibition of cardiomyocyte hypertrophy. However, inhibiting autophagy with chloroquine reversed this effect. Conclusion: The results of this study indicate that LMP10 KO attenuates Ang II-induced cardiac hypertrophic remodeling via the autophagy-dependent degradation of IGF1R and gp130, and suggests that LMP10 may be a novel therapeutic target for hypertrophic heart diseases.